2013
DOI: 10.3382/ps.2012-02670
|View full text |Cite
|
Sign up to set email alerts
|

Development of bone in chick embryos from Cobb 500 breeder hens fed diets supplemented with zinc, manganese, and copper from inorganic and amino acid-complexed sources

Abstract: Sources of Zn, Mn, and Cu (IZMC) as sulfates or as amino acid complexes (OZMC) were used to supplement Cobb 500 breeder hen diets. Experimental treatments consisted of diets supplemented with 1) 100, 100, and 10 mg/kg of Zn, Mn, and Cu, respectively, from IZMC (control); 2) 60, 60, and 3 mg/kg of Zn, Mn, and Cu, respectively, from IZMC plus 40, 40, and 7 mg/kg of Zn, Mn, and Cu, respectively, from OZMC (ISO); and 3) a diet with 100, 100, and 10 mg/kg of Zn, Mn, and Cu, respectively, from IZMC as in control plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 30 publications
0
22
2
3
Order By: Relevance
“…67 The exhausted calcium source from egg yolk for the onset of bone formation which begins at day 13 could have contributed to the formation of smaller embryos in the bioengineered eggshell, 68 indicating delayed development which in turn affected yolk absorption. Instead, poor embryo nutrition due to absence of calcium source from eggshell could have impeded the viability of the chicken embryo past day 19 as embryos at later embryonic ages appeared to be smaller and internalization of yolk appeared to be at an immature stage for the embryonic day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 The exhausted calcium source from egg yolk for the onset of bone formation which begins at day 13 could have contributed to the formation of smaller embryos in the bioengineered eggshell, 68 indicating delayed development which in turn affected yolk absorption. Instead, poor embryo nutrition due to absence of calcium source from eggshell could have impeded the viability of the chicken embryo past day 19 as embryos at later embryonic ages appeared to be smaller and internalization of yolk appeared to be at an immature stage for the embryonic day.…”
Section: Discussionmentioning
confidence: 99%
“…A developing chicken embryo derives its calcium sources from extraembryonic sources in the initial 10 days from the yolk and later from the eggshell [62][63][64][65][66] along with other trace minerals that are essential for bone formation. 67 The exhausted calcium source from egg yolk for the onset of bone formation which begins at day 13 could have contributed to the formation of smaller embryos in the bioengineered eggshell, 68 indicating delayed development which in turn affected yolk absorption. Studies have shown the administration of supplemental calcium in both quail and chicken embryos improved survival and hatching rates.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been speculated that inorganic trace element does not fulfill trace element requirements of modern poultry due to their less bioavailability and negative interaction [37,38] . Organic based trace minerals could be of value as many reports have been published on their positive effects in layer, broiler and also turkey performance [14,15,39,40] . Previous studies also revealed that efficacy of organic based trace minerals in broilers could decrease as birds age increased [41,42] .…”
Section: Discussionmentioning
confidence: 99%
“…Replacements of 30% inorganic sources of Zn, Mn, and Cu with organic sources of this microelement in broiler breeders' diet have been reported to improve humoral immune responses [12] and gastro intestinal development of their offspring's [13] . It has also been reported that supplementation of broiler breeder hen's diets with simultaneous inorganic and organic forms of Zn, Mn, and Cu had significant effects on egg shell quality, embryo mortality, some bone mineralization parameters, tibia calcification, and thickness [14,15] . Iron (Fe) is also known an essential trace mineral for all living organisms, and it is required for several metabolic processes, including oxygen and electron transport as well as DNA synthesis [16] .…”
Section: Introductionmentioning
confidence: 98%
“…The antioxidant properties of the PHE have been analyzed and reported previously by Habibian et al (2017). The content of zinc in the basal diet was determined by a flame atomic absorption spectrophotometer (Phoenix-986, AA spectrophotometer, UK) after wet ashing (Favero et al, 2013).…”
Section: Experimental Design and Purslane Extract Preparationmentioning
confidence: 99%